Frontispiece: Plasmonic Photocatalysis for CO2 Reduction: Advances, Understanding and Possibilities. Issue 25 (2nd May 2023) - Wang, Fangmu; Lu, Zhehong; Guo, Hu; Zhang, Guangpu; Li, Yan; Hu, Yubing; Jiang, Wei; Liu, Guigao
Abstract : Plasmonic photocatalysis for CO2 reduction has received intensive attention in recent years because it holds great potential for effective CO2 storage and conversion. This review summarizes the remarkable progresses on plasmonic photocatalytic CO2 reduction and the general design principles of plasmonic photocatalysts, which will help to advance the understanding and development of this promising field. More information can be found in the Review article by Y. Hu, W. Jiang, G. Liu and co‐workers. (DOI: 10.1002/chem.202202716 )